Obesity and Sex Affect the Immune Responses to Tick-Borne Encephalitis Booster Vaccination - Garner-Spitzer, Erika; Poellabauer, Eva-Maria; Wagner, Angelika; Guzek, Angela; Zwazl, Ines; Seidl-Friedrich, Claudia; Binder, Christoph J.; Stiasny, Karin; Kundi, Michael; Wiedermann, Ursula (Frontiers in Immunology, 2020)
Obesity has dramatically increased over the last 30 years and reaches according to WHO dimensions of a global epidemic. The obesity-associated chronic low-level inflammation contributes to severe co-morbidities and directly affects many immune cells leading to immune dysfunction and increased susceptibility to infections. Thus prophylaxis against vaccine-preventable diseases is crucial, yet the responsiveness to several vaccines is unclear under obesity. In order to assess the responsiveness to tick-borne encephalitis (TBE) vaccine, we re-vaccinated 37 obese individuals and 36 normal-weight controls with a licensed TBE vaccine. Metabolic, hormonal and immunologic profiles along with vaccine-specific humoral and cellular immune responses were evaluated in sera and PBMC before, 1 week, 4 weeks and 6 months after TBE-booster. Obese adults had significantly increased metabolic (triglycerides, cholesterol ratios, leptin, insulin) and pro-inflammatory (CRP) parameters. They showed stronger initial increase of TBE-specific Ab-titers (d7_d28) followed by a significantly faster decline after 6 months, which correlated with high BMI, leptin and insulin levels. The fold-increase of Ab-titer levels was significantly higher in obese compared to control males and linked to reduced testosterone levels. Obesity also affected cellular responses: PBMC of the obese vaccinees had elevated IL-2 and IFNγ levels upon antigen stimulation, indicating a leptin-dependent pro-inflammatory Th1 polarization. The expansion of total and naïve B-cells in obese might explain the initial increase of Ab-titers, while the reduced B-memory cell and plasma blast generation could be related to fast Ab decline with a limited maintenance of titers. Among Tfh cells, the Tfh17 subset was significantly expanded particularly in obese males, where we observed a strong initial Ab increase. Systemic but not local vaccine side effects were more frequent in obese subjects as a possible consequence of their low-grade pro-inflammatory state. In summary, TBE booster vaccination was effective in obese individuals, yet the faster Ab decline could result in a reduced long-term protection. The sex-based differences in vaccine responses indicate a complex interplay of the endocrine, metabolic and immune system during obesity. Further studies on the long-term protection after vaccination are ongoing, and also evaluation of primary vaccination against TBE in obese individuals is planned.